The Potential Therapeutic Value of Renin-Angiotensin System Inhibitors in the Treatment of Colorectal Cancer - Tabatabai, Ehsan; Khazaei, Majid; Parizadeh, Mohammad R.; Nouri, Mohammad; Hassanian, Seyed M.; Ferns, Gordon A; Rahmati, Mohammad; Avan, Amir (Current Pharmaceutical Design, 2022)
Colorectal cancer is the third most common cancer globally. Despite extensive preclinical and clinical studies, it is still among the leading causes of cancer-related death, and a need for new therapeutic options is required. The renin-angiotensin system plays an important role in regulating blood pressure and cell growth. In addition to their hemodynamic effects, some of the renin-angiotensin system components, such as angiotensin, are also growth factors that promote cell proliferation and angiogenesis, and its dysregulation is reported to be associated with poor prognosis in colorectal cancer. Here we describe the critical role of the renin-angiotensin system pathway in colorectal cancer as well as the preclinical and clinical investigations renin-angiotensin system inhibitors: angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers as a potential therapeutic target in the treatment of colorectal cancer. Several studies have been shown that the inhibition of these pathways can reduce tumor growth and metastasis; however, some of the data remain inconsistent. There is accumulating evidence of the therapeutic potential of some inhibitors, such as Losartan which are now in clinical phases in the treatment of several malignancies using Nivolumab in combination with FOLFIRINOX in pancreatic cancer. Further investigations are warranted to improve the efficacy and selectivity of current and future anticancer strategies targeting renin-angiotensin systems.
Keywords: Colorectal cancer